Analisis Populasi Tanaman Bayam Cabut (Amaranthus Spp. L.) dan Sawi Hijau (Brassica juncea L.) pada Sistem Bertanam Vertikultur - ASIH, NI LUH BUDI; DHARMA, I PUTU; KESUMADEWI, ANAK AGUNG ISTRI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.9, No.3, Juli 2020, 2020)
The Population Analysis of Spinach ( Amaranthus Spp. L) and Green Mustard ( Brassica Juncea L.) Crops on Verticulture System   Production of spinach and mustard greens in Denpasar is still low. The effort to increase the vegetables production need to be done with a verticultural system but the crops population should be considered. Therefore, a greenhouse experiment to find out the optimal population of spinach and mustard greens grown under verticulture system had done on July - November 2016 in Denpasar. The experiments was conducted using randomized split block design with three replications.The treatments were consisting spinach and green mustard as the main plot and the additional factor consisted of five population levels, namely 8, 12, 16, 20 and 24 plants per container. The total number of experimental units was 30. The population effect of spinach and mustard greens was shown on fresh weight variables per plant which were analyzed by regression analysis. The results of the regression analysis on fresh weight variables per plant showed that the population negatively affected the fresh weight of spinach plants per plant and had a positive effect on the fresh weight of green mustard plants per plant.